Biomechanics optimisation of the laminoplasty groove size and position: A numerical study - Hrouda, Ales; Capek, Lukas; Hradil, Jan; Horak, Zdenek (Journal of clinical neuroscience, 2022)
BACKGROUND: This study is focused on the opening technique of the cervical vertebrae during laminoplasty which serves to substantially reduce the most severe adverse effects of the simple resection of posterior vertebral elements. This computational study aims to clarify by an optimisation approach what shape and position upon the lamina the groove should have. METHODS: The computational model was developed in the computational software COMSOL Multiphysics 5.6a based on a computer tomography data obtained from the C4 vertebra. For finding the optimal minimum or maximum of a function (surface), optimisation algorithms are developed following the Nelder-Mead algorithm. RESULTS: The reaction-opening force increases with a decreasing groove radius and an increasing position from the vertebra body. The created area increases with a decreasing groove radius and a decreasing position. As the opening happens mostly only above the groove, the opening area increases only in this location. Moreover, the von Mises stress peak value is almost twice as large as in the case of maximization of the opening area, which might result in breaking of the lamina as the thickness of the lamina would be reduced to its minimum. CONCLUSION: The groove radius and position can affect the opening force and the opening area in case of double door laminoplasty. The opening force is highly influenced by the groove position and radius. The best position for placing the groove is in the middle of the lamina and the radius of the groove should be as large as possible.
Keywords: Laminoplasty; biomechanika; Biomechanical Phenomena; krční obratle; finite element method; algoritmy; groove position; Humans; počítačová rentgenová tomografie; Algorithms; Cervical Vertebrae; spine; Tomography, X-Ray Computed; lidé; optimisation; laminoplastika